Removal of phosphate from aqueous solutions by electro-coagulation - Bektas, N; Akbulut, H; Inan, H; Dimoglo, A (Elsevier, 2004)
The aim of this paper was to investigate the feasibility of the removal of phosphate from aqueous solution by electro-coagulation (EC). The current density (CD) between 2.5 and 10 mA cm(-2) and duration in the limits of 5-20 min were tried for different concentrations. In order to determine optimal operating conditions, the EC process used for the phosphate removal was examined in dependence with the CD, initial concentrations and time. The results of the experimental batch processing showed high effectiveness of the EC method in removing phosphate from aqueous solutions. 2003 (C) Elsevier B.V. All rights reserved.
Keywords: phosphate; electro-coagulation; water treatment; nutrient removal; Al electrode